2021
DOI: 10.1007/s10072-021-05218-x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal neurological pupil index is associated with malignant cerebral edema after mechanical thrombectomy in large vessel occlusion patients

Abstract: Background and objectives Malignant cerebral edema (MCE) is a feared complication in patients suffering from large vessel occlusion. Variables associated with the development of MCE have not been clearly elucidated. Use of pupillometry and the neurological pupil index (NPi) as an objective measure in patients undergoing mechanical thrombectomy (MT) has not been explored. We aim to evaluate variables significantly associated with MCE in patients that undergo MT and hypothesize that abnormal NPi is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Admission plasma glucose has been demonstrated to be a risk factor associated with CED after acute ischemic stroke in previous studies (Shimoyama et al, 2014;Cheng et al, 2020;Dowlati et al, 2021). However, our findings showed that the RPG was not associated with this outcome, while the SHR was independently associated with a higher degree of CED, 90-day poor functional outcome, and 90-day death, and the predictive value of the SHR (as a continuous variable) for moderate-tosevere CED and 90-day poor functional outcome, indicated by the AUC, was better than that of the RPG or FPG.…”
Section: Discussionmentioning
confidence: 94%
“…Admission plasma glucose has been demonstrated to be a risk factor associated with CED after acute ischemic stroke in previous studies (Shimoyama et al, 2014;Cheng et al, 2020;Dowlati et al, 2021). However, our findings showed that the RPG was not associated with this outcome, while the SHR was independently associated with a higher degree of CED, 90-day poor functional outcome, and 90-day death, and the predictive value of the SHR (as a continuous variable) for moderate-tosevere CED and 90-day poor functional outcome, indicated by the AUC, was better than that of the RPG or FPG.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, abnormal NPi values ( < 3.0) on the ipsilateral side of stroke lesions within 72 hours after mechanical thrombectomy had a strong independent association with malignant cerebral edema in patients with large vessel occlusion (odds ratio, 21.80; 95% confidence interval [CI], 3.32-286.4) [1].…”
Section: Monitoring In Patients With Increased Icp and Strokementioning
confidence: 98%
“…In particular, evaluating PLR ≥ 72 hours after the return of spontaneous circulation (ROSC) using a quantitative pupillometer is emerging as a helpful examination to evaluate brainstem function in post-CA patients [26,27]. Several studies have evaluated the relationship between pupillometer parameters and prognostication following CA (Table 2) [1,11,12,[28][29][30][31][32][33][34][35]. A prospective study of out-of-hospital cardiac arrest (OHCA) patients treated with targeted temperature management (TTM) at 33°C with sedation and neuromuscular blocking agents reported that the quantitative %CH on days 1 and 2 were associated with poor outcomes at 90 days (cerebral performance categories [CPCs] 3-5).…”
Section: Prognosis In Patients With Post-cardiac Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, there are only few studies assessing the prognostic performance of automated pupillometry in ischemic stroke patients, and the exact time-point of pupillary light reflex deterioration in relation to EVT has so far not been analyzed in these studies [ 13 , 14 , 19 ]. The clinical value of this non-invasive technique especially in the early phase after EVT in LVO patients is therefore still not fully evaluated.…”
Section: Introductionmentioning
confidence: 99%